Femtosecond laser treatment promotes the surface bioactivity and bone ingrowth of Ti6Al4V bone scaffolds - Wang, Su; Zhang, Miao; Liu, Linlin; Xu, Rongwei; Huang, Zhili; Shi, Zhang’ao; Liu, Juncai; Li, Zhong; Li, Xiaohong; Hao, Peng; Hao, Yongqiang (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, a femtosecond laser with an 800 nm wavelength was used to modify the surface of a titanium alloy bone scaffold created via selective laser melting (SLM). The outcomes demonstrated that the surface morphology of the bone scaffold after femtosecond laser treatment was micro-nano. The hydrophobic structure of the scaffold was changed into a super hydrophilic structure, improving the surface roughness, which was highly helpful for osteoblast adhesion and differentiation. Femtosecond laser surface treatment in vitro samples produced a thick layer of hydroxyapatite (HAP) with improved surface bioactivity. The effectiveness of osseointegration and interstitial growth of the specimens treated with femtosecond laser surface were found to be better when bone scaffolds were implanted into the epiphysis of the tibia of rabbits. As a result, femtosecond laser therapy dramatically enhances the surface activity of bone scaffolds and their capacity to integrate with the surrounding bone tissues, serving as a trustworthy benchmark for future biological scaffold research.